2018
DOI: 10.1016/j.jcrysgro.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of single crystal growth of candidate quantum spin-ice Pr2Hf2O7

Abstract: We report the optimized conditions for growing the high quality single crystals of candidate quantum spin-ice Pr2Hf2O7 using the optical floating-zone method. Large single crystals of Pr2Hf2O7 have been grown under different growth conditions using a four-mirror type optical floating-zone furnace and their microscopic structural differences have been probed by high-resolution synchrotron x-ray diffraction (SXRD). The SXRD data reveal that the crystals grown under flowing argon (∼ 2 L/h) atmosphere with slightl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Nd 2 Zr 2 O 7 reveals the coexistence of an ordered and fluctuating Coulomb phase at lowtemperature [10]. Dy 2 Zr 2 O 7 , Tb 2 Hf 2 O 7 and Pr 2 Hf 2 O 7 remain dynamic down to 100 mK [11][12][13]. However the Dy 2 Zr 2 O 7 and Pr 2 Hf 2 O 7 have been shown to exhibit glassy transition at ∼90 mK [11,17].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nd 2 Zr 2 O 7 reveals the coexistence of an ordered and fluctuating Coulomb phase at lowtemperature [10]. Dy 2 Zr 2 O 7 , Tb 2 Hf 2 O 7 and Pr 2 Hf 2 O 7 remain dynamic down to 100 mK [11][12][13]. However the Dy 2 Zr 2 O 7 and Pr 2 Hf 2 O 7 have been shown to exhibit glassy transition at ∼90 mK [11,17].…”
Section: Introductionmentioning
confidence: 98%
“…In order to understand the spin-ice state, researchers have begun to look outside the present structural map scenario by forming the stuffed pyrochlores by placing a non-magnetic atom or the atoms with smaller moments in the pyrochlore lattice [8][9][10][11][12][13][14]. In pyrochlore oxide A 2 B 2 O 7 , various combinations of A and B site ions are employed to replace the existing spin ice state and disorder the symmetry of available crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…Some extensive works have been carried out regarding the lowtemperature heat capacity measurements, for example, up to 300 K. The low-temperature heat capacity of La 2 Hf 2 O 7 compound with pyrochlore structure was investigated by Kopan et al 7 (57-302 K) and Guskov et al 8 (15-346 K) by adiabatic calorimetry and Anand et al 9 using PPMS (1.8-300 K). The heat capacity of Pr 2 Hf 2 O 7 was investigated in the temperature range 0-25 K by Craig 10 (although the experimental method is not described in the thesis), Yaraskavitch, 11 Sibille et al, 12 Anand et al 13,14 (1.8300 K), and Guskov et al 15 in the larger temperature ranges. Low-temperature adiabatic calorimetry was applied by Guskov et al 16 for the determination of heat capacity of Nd 2 Hf 2 O 7 (18.9-347.6 K) and in the earlier work by Anand et al 9 can be found the data from PPMS measurements.…”
Section: Introductionmentioning
confidence: 99%
“…using PPMS (1.8–300 K). The heat capacity of Pr 2 Hf 2 O 7 was investigated in the temperature range 0–25 K by Craig 10 (although the experimental method is not described in the thesis), Yaraskavitch, 11 Sibille et al., 12 Anand et al 13,14 . (1.8300 K), and Guskov et al 15 .…”
Section: Introductionmentioning
confidence: 99%